2009
DOI: 10.1007/s10198-009-0151-8
|View full text |Cite
|
Sign up to set email alerts
|

The economics of cochlear implant management in France: a multicentre analysis

Abstract: This study assessed the direct medical cost of cochlear implantation in children and adults in France. A prospective multicentre study involving 19 French University Hospitals included 268 children and 201 adults who were severely to profoundly hearing-impaired. Medical resources utilisation included diagnostic tests, in-patient care, device implants, adverse events and follow-up visits for rehabilitation in the 1st year. The mean costs were 34,686 per child and 31,946 per adult. The cost of device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The cochlear implant system was the greatest single cost involved in the implantation process. This result was similar to the findings in a recent French study, which also reported the cost of the device as the main cost in implantation (Molinier, Bocquet, Bongard & Frayesse, 2009). In that study the cost of the device represented 64.4% and 68.8% of the total cost for children and adults respectively.…”
Section: Cochlear Implant System Costs Over Timesupporting
confidence: 91%
“…The cochlear implant system was the greatest single cost involved in the implantation process. This result was similar to the findings in a recent French study, which also reported the cost of the device as the main cost in implantation (Molinier, Bocquet, Bongard & Frayesse, 2009). In that study the cost of the device represented 64.4% and 68.8% of the total cost for children and adults respectively.…”
Section: Cochlear Implant System Costs Over Timesupporting
confidence: 91%
“…Sixteen studies were carried out in Europe [27, 9, 10, 1214, 2427], 7 in North America [7, 1517, 19, 20, 22], 2 in Asia [28, 29], and 1 in Australia [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were cost analysis studies [24, 9, 19, 24, 25, 27], and 18 were global economic evaluations, including 16 cost-utility analyses [58, 10, 1216, 2023, 28, 29] and 2 costs-benefit analysis [17, 26]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations